Penggunaan Media Lift The Flap Book untuk Meningkatkan Penguasaan Kosakata pada Anak Tunarungu di SLB Negeri Buol Sulawesi Tengah - Ramadhan, Moh Daroes; Sulasminah, Dwiyatmi; Mustafa, Mustafa (JURNAL ORTO DIDAKTIKA, 2025)
This research examines the low ability to master vocabulary in class V deaf children at SLB Negeri Buol. The aim of this research is to find out: 1) The ability to master vocabulary in deaf children before using lift the flap book media. 2) The ability to master vocabulary in deaf children after using lift the flap book media. 3) The process of using lift the flap book media to increase vocabulary mastery abilities in deaf children. 4) Increased ability to master vocabulary in deaf children after using lift the flap book media. This research is quantitative research and a descriptive type of research. The data collection technique is a test. The subject of this research was a deaf child in class V. The data analysis technique was descriptive. The results of the research show that 1) The ability to master vocabulary before using lift the flap book media is in the very poor category, 2) The ability to master vocabulary after using the lift the flap book media is in the very good category, 3) The process of using the lift the flap book media increases vocabulary mastery in deaf children, 4) Using the lift the flap book media can increase the ability to master vocabulary in children deaf class V at SLB Negeri Buol.